Pengaruh Literasi Keuangan dan Manajemen Rantai Pasok Terhadap Keberlanjutan Usaha: Studi pada Pelaku Usaha Kecil dan Menengah di Kabupaten Bandung (Jurnal Riset Manajemen dan Akuntansi, 2025)
SMEs play a strategic role in the national economy but often challenges in maintaining their business continuity, particularly due to intense competition and rapid technological changes. This study aims the influence of Financial Literacy And Supply Chain Management On Business Sustainability Among Small And Medium Enterprises (SMEs) in bandung Regency. Financial literacy refers to the ability of business actors to understand and manage finances effectively, including decision-making related to expenses, savings, investments, and insurance. Meanwhile, supply chain management involves handling the flow of goods, information, and processes from production to distribution. This research employs a quantitative approach using a survey method involving 111 SMEa respondents, with data analyzed through multiple regression. The findings indicate that both financial literacy and supply chain management have a positive and significant effect on business sustainability, both partially and simultaneously. These result highlight the importance of enhancing SMEs capabilities in financial management and supply chain efficiency to improve competitiveness and ensure long-term business sustainability.